2019
DOI: 10.1038/s41598-019-53006-7
|View full text |Cite
|
Sign up to set email alerts
|

CBX2-dependent transcriptional landscape: implications for human sex development and its defects

Abstract: Sex development, a complex and indispensable process in all vertebrates, has still not been completely elucidated, although new genes involved in sex development are constantly being discovered and characterized. Chromobox Homolog 2 (CBX2) is one of these new additions and has been identified through a 46,XY girl with double heterozygous variants on CBX2.1, causing Differences of Sex Development (DSD). The mutated CBX2.1 failed to adequately regulate downstream targets important for sex development in humans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Alterations in some of these genes could be associated with the diverse clinical manifestations in PN patients, such as lower expression of CBX2, SEMA3A and NEURL3 with hypogonadism [37][38][39] and lower expression of transcription factor GATA2 and regulatory gene CEBPZOS with leukopenia/ monocytopenia as in MonoMAC syndrome. 40,41 Differentiation of monocytes from haematopoietic progenitor cells involves several transcription factors, including GATA2, IRF8, KLF4 and Spl1.…”
Section: Pn Patients Had Distinct Patterns Of Alterations In Gene Exp...mentioning
confidence: 99%
“…Alterations in some of these genes could be associated with the diverse clinical manifestations in PN patients, such as lower expression of CBX2, SEMA3A and NEURL3 with hypogonadism [37][38][39] and lower expression of transcription factor GATA2 and regulatory gene CEBPZOS with leukopenia/ monocytopenia as in MonoMAC syndrome. 40,41 Differentiation of monocytes from haematopoietic progenitor cells involves several transcription factors, including GATA2, IRF8, KLF4 and Spl1.…”
Section: Pn Patients Had Distinct Patterns Of Alterations In Gene Exp...mentioning
confidence: 99%
“…Later, the CBX2.1 and CBX2.2 transcriptional landscape was further expanded through protein/DNA interaction studies of CBX2 binding partners, coupled with in vitro functional analysis of downstream gene targets in human pre-granulosa (KGN) and Sertoli-like cells (NT2/ D1), adding to the repertoire of CBX2-regulated factors [Bouazzi et al, 2019;Sproll et al, 2019]. The selected genes and their respective role during development or association with DSD is summarized in Table 1.…”
Section: Opposite Sides Of the Same Coinmentioning
confidence: 99%
“…Previous reports suggested that CBX2, a member of PcG, was an epigenetically modified transcriptional repressor. Recently, it was also found to serve as a transcriptional activator to regulate the expression of downstream genes [12,13]. However, the functional role of cbx2 in gonadal development is still unclear in vertebrates other than mammals.…”
Section: Introductionmentioning
confidence: 99%